Implementation of Traditional Games to Reduce Sedentary Behavior of Elementary School Students - Ilham Muhamad Nasir; Ayi Suherman; Tedi Supriyadi (Universitas Negeri Semarang, 2026)
The development of digital technology and the increasing use of electronic devices in elementary school children contribute to the increase in sedentary behavior which has an impact on decreased physical fitness, impaired motor development, and reduced social interaction. This study aims to analyze the effectiveness of the implementation of traditional games in reducing the sedentary behavior of elementary school students. The study uses a quantitative approach with a quasi-experimental design through a nonequivalent control group design model. The study participants totaled 77 students in grades IV–VI consisting of the experimental group (n = 39) and the control group (n = 38). The instrument used was the Adolescent Sedentary Activity Questionnaire (ASAQ) which met the criteria of validity and reliability (α = 0.853). Traditional game-based learning interventions were carried out for ten meetings in PE learning. Data analysis was conducted using the Wilcoxon Signed Rank Test and the Mann–Whitney U Test at a significance level of 0.05. The results showed a significant decrease in sedentary behavior in the experimental group, from 4.32 hours/day to 3.06 hours/day. These findings suggest that traditional games are effective as a learning strategy to lower the sedentary behavior of elementary school students.